PELATIHAN DESAIN KEMASAN MAKANAN DAN MINUMAN UNTUK KEAMANAN DAN KUALITAS PRODUK PADA KELOMPOK PKK DUSUN BATU BINTANG - N.K. Seminari; I.N. Nurcaya; L.G.S. Artini; N.M. Rastini (Buletin Udayana Mengabdi, 2023)
People's behavior since the pandemic has changed a lot. Health is the main priority factor for the community, both in daily activities, traveling, to choosing the products to buy. One of the important aspects that consumers pay attention to is product packaging. The packaging of food and beverage products is currently still receiving little attention from the food producer groups in Batu Bintang Hamlet. The service is carried out to the PKK group in Batu Bintang Hamlet, most of which sell their processed food around the stalls in the Batu Bintang Hamlet area. The activity was carried out on Sunday, July 24, 2022. The location of the activity was in Dusun Batu Bintang, Dauh Puri Klod Village, Denpasar City. The activity presented speakers from the Denpasar City Department of Industry and Trade. The presentation on Marketing and Financial Management was conducted by a lecturer at the Faculty of Economics and Business. This service activity has benefited the Banjar Batu Bintang PKK group in improving product cleanliness, safety, quality, and productivity. Participants hope that community service activities like this will be carried out more intensively. Keywords: Design, packaging, safety, and quality.